Soil-Friendly Education in Nepal: Mythology Vs Reality (Shiksha Shastra Saurabh, 2025)
This study aims to explore the relevance, integration of soil friendly content, and impact of soil-suited education within Nepal’s school education and curriculum across diverse socio-cultural and ecological contexts. To furnish this study mixed method was adopted and within qualitative design geographical phenomenological study was used with direct field visit as primary data and observation. Direct interview was conducted with twenty teachers and fifteen school management committee members from Darchula, Surkhet, Dang, Taplejung, Kailali and Kalikot district. The perspective was calculated in percentile ranking interpretation as quantitative analysis. The study concludes that, there is a huge gap in soil friendly education in school curriculum with relevant contents, that created bundles of problems and crisis in the education system of Nepal but the Hinduism, Buddhism, Islamic Quran, Bible and Christianity have more focused on soil and land as mother, God and Goddess praying as the powerful source and truth and treasure of divine and prosperity. Soil-suited education and curriculum is a truth according to philosophical base. It is reality not a mythology. We are unable to include the truth of soil within school education and curriculum. To resolve the problem policy makers, need to be implement the best guideline of mentioned philosophies and theories for the development of soil-friendly education (Mato Suhaudo Sikshya) in Nepal.